Initial design of math apache based-learning in tourism for SMK students - Gusti Ayu Dessy Sugiharni; Putu Herny Susanti (Universitas Pendidikan Ganesha, 2025)
This study aimed to develop a conceptual framework for an Apache-based mathematics learning platform contextualized with the vocational needs of SMK Tourism. The Research and Development (R&D) method with the ADDIE model produces a system design that includes needs analysis, architecture design, and prototype validation. Data collection used questionnaires (524 SMK Tourism students), in-depth interviews (20 teachers), and literature studies related to open-source technology. The results showed that 77.6% of students needed an applied mathematics approach with a tourism case study. The system design was a web-based interactive module (Apache + Moodle) with a contextual quiz feature. Material experts' validation assessed 87% of the content's suitability to the SMK curriculum. Technology experts confirmed technical feasibility with mobile optimization recommendations. Critical findings revealed that this approach effectively solved the gap between abstract mathematical theory and the practical needs of the tourism industry.